Gender dynamics and adoption of agricultural innovations in Fatick: The case of mycorrhizal inoculum in Diossong (Fatick) - Sidy Mohamet, Faye; Dione, Geneviève; Diallo, Ibrahima; Rietveld, Anne; Piraux, Marc (2024)
This study explores gender dynamics and their effect on the adoption of mycorrhizal inoculum in Diosong, a commune in the Fatick region. This choice is justified by the vital importance of the agricultural sector in this region and the difficulties faced by farmers. Indeed, according to the ANSD report (2024), the Fatick region, which is predominantly agricultural (with 63,880 farming households, or 92% of ordinary households), faces major challenges. These stem from the predominance of traditional farming practices and heavy reliance on rainfed agriculture, making the region particularly vulnerable to the impacts of climate change (Diop, 2017). These challenges underscore the need to adopt sustainable agricultural innovations, such as mycorrhizal inoculum, to enhance the resilience and sustainability of farming systems (Odru, 2013; Lericollais, 1989).